Archaea predominate in the ammonia oxidation process in the sediments of the Yap and Mariana Trenches - Liu, Hao; Jing, Hongmei; Wang, Fangzhou (Frontiers in Microbiology, 2023)
Ammonia-oxidizing archaea (AOA) and bacteria (AOB) play an important role in oxidizing ammonia to nitrite in different marine environments, however, their relative contribution to the ammonia oxidation in the deep-sea sediments was still largely unknown. Sediment samples from seamounts and the Challenger Deep along the arc of the Yap Trench and the Mariana Trench were used for the investigation of the geographical distribution of AOA and AOB at the cDNA level with associated potential nitrification rates (PNRs) being measured. AOA was predominated by Candidatus Nitrosopumilus and Nitrosopumilaceae, while Methylophaga was the major group of AOB. Significantly higher transcript abundance of AOA amoA gene than that of AOB appeared in all samples, corresponding to the much higher RNRs contributed by AOA. Both the total and AOA PNRs were significantly higher in the deeper layers, and were very likely due to the high sensitivity of AOA to ammonia and oxygen than AOB. In the surface layers, TN and TOC had significant positive and negative effects on the distributions of the AOA amoA gene transcripts, respectively, while NH4 + concentration was positively correlated with the AOB amoA gene transcripts. Our study demonstrated that AOA played a more important role than AOB in the ammonia-oxidizing process occurred in the sediments of the Yap and Mariana Trenches, and would expand the understanding of their ecological contribution to the nitrification process and nitrogen flux of trenches.